2006
DOI: 10.1111/j.1464-5491.2006.01964.x
|View full text |Cite
|
Sign up to set email alerts
|

Maternal glucose levels influence birthweight and ‘catch‐up’ and ‘catch‐down’ growth in a large contemporary cohort

Abstract: Random maternal glucose concentrations (taken at 28 weeks' gestation) in the normal range are positively related to birthweight. Glucose concentrations also predict greater weight and length in infancy. Despite this, babies born to mothers with higher glucose concentrations within the normal range show significant 'catch-down' growth in infancy as shown by a fall in weight SDS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 32 publications
3
9
0
Order By: Relevance
“…Regarding growth trajectories in early childhood, earlier studies demonstrates a catch-down growth from birth to a few months of age in children to diabetic mothers 24 , 25 . Even in children to non-diabetic mothers the growth pattern of catch-down growth in children to mothers with the highest glucose levels, within normal range, has been observed 17 . As in our study, Stenhouse et al showed a catch-down growth in children to non-diabetic mothers from birth to 6–9 months of age that correlated with the highest thirtile, within normal range, of randomly collected venous glucose levels in pregnancy week 28.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding growth trajectories in early childhood, earlier studies demonstrates a catch-down growth from birth to a few months of age in children to diabetic mothers 24 , 25 . Even in children to non-diabetic mothers the growth pattern of catch-down growth in children to mothers with the highest glucose levels, within normal range, has been observed 17 . As in our study, Stenhouse et al showed a catch-down growth in children to non-diabetic mothers from birth to 6–9 months of age that correlated with the highest thirtile, within normal range, of randomly collected venous glucose levels in pregnancy week 28.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, they examined the relationship between the level of randomly collected venous glucose, within normal range, in gestational week 28 and childhood growth. They observed a catch-down growth in children from birth to 24–36 weeks of post-natal age in children with mothers having a glucose level within the highest third of normal range 17 . Another study provided some evidence that maternal glucose levels within normal ranges during pregnancy correlate positively to adiposity in 10–14 year old children 18 .…”
Section: Introductionmentioning
confidence: 99%
“…In the child, GDM has been found to increase the risk of neonatal hypoglycaemia, hyperbilirubinaemia and a birthweight above the 90th percentile . Also, infants born to mothers with higher glucose concentrations have been shown to have a significant catch‐down weight in infancy . Some of these infants, but not all, may need to be supplemented with infant formula and hospital procedures on the management of these conditions may affect breastfeeding .…”
Section: Discussionmentioning
confidence: 99%
“…[ 4 , 5 , 53 ] This slowed postnatal growth pattern is called “catch-down” growth, and refers to a growth pattern during infancy subsequent to exposure of the fetus to excess nutritional or metabolic substrates in utero [ 54 ]. This early growth pattern is strongly influenced by a drive to compensate for the intrauterine effects on the fetus of the maternal metabolism associated with obesity and glucose intolerance [ 55 ]. It is not known whether postnatal feeding method, (i.e., breastfeeding compared with formula feeding) further slows postnatal growth among GDM offspring.…”
Section: Introductionmentioning
confidence: 99%